Characteristics of a population-based multiple sclerosis cohort treated with disease-modifying drugs in a universal healthcare setting. (2nd January 2021) - Ng, Huah Shin; Zhu, Feng; Kingwell, Elaine; Zhao, Yinshan; Yao, Shenzhen; Ekuma, Okechukwu; Svenson, Lawrence W; Evans, Charity; Fisk, John D.; Marrie, Ruth Ann; Tremlett, Helen
ABSTRACT: Background : Relatively little is known about the use of disease-modifying drugs (DMDs) for multiple sclerosis (MS) in the population-based universal healthcare setting. This study aimed to describe the characteristics of a population-based cohort with MS and their DMD exposure in four Canadian provinces. Methods : We identified all adults (aged ≥18 years) with MS using linked population-based health administrative data. Individuals were followed from the most recent of their first MS or demyelinating event or 1 January 1996(study entry), to the earliest of death, emigration, or 31 March 2018(study end). Cohort characteristics examined included sex, age, socioeconomic status, and comorbidity burden. Results : Overall, 10, 418/35, 894 (29%) of MS cases filled a DMD prescription during the 22-year study period. Most were women (n = 7, 683/10, 418;74%), and 17% (n = 1, 745/10, 418) had some comorbidity (Charlson Comorbidity Index≥1) at study entry. Nearly 20% (n = 1, 745/10, 418) were aged ≥50 when filling their first DMD; the mean age was 39.6 years. Conclusions : Almost 1 in 6 people with MS had at least some comorbidity, and nearly 1 in 6 were ≥50 years old at the time of their first DMD. As these individuals are typically excluded from clinical trials, findings illustrate the need to understand the harms and benefits of DMD use in these understudied groups.